The discovery of novel coronaviruses in bat guano, Sarawak, Malaysian Borneo - Tan, Cheng Siang; Noni, V.; Anwarali-Khan, F.A.; Denel, A.; Sathyiya Seelan, J.S. (International Society for Infectious Diseases, 2022)
Purpose Virological surveillance was conducted in to determine the presence of bat CoVs in the bat population in Wind Cave Nature Reserve, Sarawak, Malaysian Borneo.